المدارس القرآنية وأثرها في تقويم سلوك التلميذ وملكته اللغوية - بن عائشة, صارة (كلية الأدب العربي والفنون, 2024)
تلعب المدارس القرآنية دورا هاما في تقويم سلوك التلميذ وملكته اللغوية، بحيث تغرس في نفوس الأطفال والتلاميذ القيم الاجتماعية التي تساهم في بناء شخصيتهم مستقبلا، وتساعدهم في التطلع إلى المثل العليا والأهداف الكبرى في الحياة، فهي تعتني بتعليم القرآن الكريم والقيم الإسلامية، مما يساهم في بناء شخصية التلميذ وتعزيز قيم الأخلاق والتسامح والتواضع. بالإضافة إلى ذلك دراسة القرآن تعتبرا تحفيزا لتطوير مهارات اللغة العربية وزيادة الفهم والتحليل اللغوي، مما يعزز ملكة التلميذ اللغوية ويساعده في التعبير بوضوح ودقة، وفي هذا البحث ركزنا على الدور الفعال الذي تلعبه المدارس القرآنية في إرساء كفاءة التواصل والملكة اللغوية وكيف تؤثر على سلوك التلميذ Koranic schools play an important role in evaluating a pupil's behaviour and linguistic property, instilling in children and pupils the social values that contribute to building their personality in the future, helping them aspire to the ideals and grand goals of life. They care for the teaching of the Holy Koran and Islamic values, thus contributing to building the personality of the pupil and promoting the values of morality, tolerance and humility. In addition, the Qur 'an study is a catalyst for the development of Arabic language skills, increased understanding and linguistic analysis, thus enhancing the queen of the pupil and helping him to express clearly and accurately. In this research, we focused on the effective role played by Koranic schools in establishing the efficiency of communication and linguistic queen and how it affects the behaviour of the pupil.
Keywords: المدارس القرآنية- الاكتساب اللغوي- السلوك- الملكة اللغوية.; Koranic schools - language acquisition - behaviour - linguistic queen.